Ruth Landes : a life in anthropology - Cole, Sally Cooper, 1951- (Critical studies in the history of anthropology., 2003)
"Ruth Landes (1908-91) is now recognized as a pioneer in the study of race and gender relations. In Ruth Landes, Sally Cole reconsiders Landes's life, work, and career, and places her at the heart of anthropology."